Hulk (2008), volume 4 ebook Hulk vs. x-force. - Loeb, Jeph (Hulk (2008), 2012)
Collects Hulk (2008) #14-18. CODE RED! One person may know the secret of Red Hulk's identity. And X-Force is protecting her! More than ever, Red Hulk needs a little help from his friends - the best friends money can buy! Punisher vs. X-23! Crimson Dynamo vs. Archangel! Thundra vs. Domino! Deadpool vs. Warpath! Red Hulk vs. Wolverine! Topping it off is Elektra on the side of Team Hulk, but whose side is Red She-Hulk on? Author: Jeph Loeb. Illustrator: Ian Churchill, Whilce Portacio. © 2019 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com